Environmental Governance and Sustainable Business Development: Case Of Nestle El Jadida O. El Gueddar, T.Aarab, A. Sahib Eddine, F. Rahmouni, - A. Aajjane, O. El Gueddar, r, T.Aarab, A. Sahib Eddine, F. Rahmouni (International Journal of Scientific Research and Management (IJSRM), 2017)
the Enterprise Allows Guarantee Process unsustainable and efficient of value creation accordance with of all parties - internal and external stakeholder and meet règlementslegaux, statutes and the internal Ethical Principles. Environmental Governance is the One Major concerns of company directors. For practicing, those are many in adopting organizational measures recommended by the overall policy of the company. We interested us in this article to environmental practices and the role assigned to the direction of flow analyzer environmental governance in the making Nestlé El Jadida by the analysis of its environmental policy based on the environmental management system ISO 14001 standards according. Environmental governance is not hot topic for the seekers in management science and environment. The implementation of this Governance in